Hubungan Pola Asuh Orang Tua dengan Kenakalan Remaja di SMA Negeri 8 Surakarta - Sri Sayekti Heni Sunaryanti - AKPER Mamba’ul ‘Ulum Surakarta (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2016)
Abstract: Adolescence is an in-between period which bridges the childhood to the adulthood. The parents shall give more attention to this epoch. When it is not responded, the youth can be susceptible to moral and ethical deviations, which can ruin their selves. In their ten teenage years, the awareness of the youth belongs to entropy (a condition in which human awareness has not been well arranged). The objective of this research is to investigate the correlation between the parenting pattern and the juvenile delinquency at State Senior Secondary School 8 Surakarta.This research used the descriptive correlational method with an analytical survey approach. It was conducted at State Senior Secondary School 8 Surakarta from March 10th to April 10th, 2013 in academic year 2012/2013. The population of the research was all of the 960 students of State Senior Secondary School 8 Surakarta. The samples of the research were 91 students. The results of the research are as follows: (1) the parenting pattern at State Senior Secondary School 8 Surakarta belongs to good category (50.5%); (2) The juvenile delinquency of the students of State Senior Secondary School 8 Surakarta is in the low category (45.1%); and (3) there is a significant correlation between the parenting pattern and the juvenile delinquency at State Senior Secondary School 8 Surakarta as indicated by t = -0.520; Zcount = -7.300 < -2.85; p = 0.000 < 0.05. Based on the results of the research, a conclusion is drawn that the parenting pattern has a correlation with the juvenile delinquency at State Senior Secondary School 8 Surakarta.Keywords: Parenting pattern and juvenile delinquency. Abstrak: Remaja merupakan masa transisi dari anak-anak menuju dewasa, masa ini harus lebih diperhatikan oleh orang tua karena apabila tidak ditanggapi, remaja dapat melakukan penyimpangan-penyimpangan moral dan etika yang dapat merusak dirinya sendiri. Dalam masa remaja sifat kesadarannya masih entropy (keadaan dimana kesadaran manusia belum tersusun rapi) walaupun isinya sudah banyak (ilmu pengetahuan, perasaan, dan sebagainya). Tujuan untuk mengetahui hubungan antara pola asuh orang tua dengan kenakalan remaja di SMA Negeri 8 Surakarta. Jenis penelitian ini adalah deskriptif korelatif dengan metode survey analitik. Penelitian ini dilaksanakan pada tanggal 10 Maret sampai 10 April 2013 di SMA Negeri 8 Surakarta tahun ajaran 2012/2013. Populasi penelitian ini adalah seluruh siswa SMA Negeri 8 Surakarta yang berjumlah 960 siswa, adapun sampel penelitian adalah 91 siswa. Pola asuh orang tua di SMA Negeri 8 Surakarta termasuk kategori baik (50,5%). Siswa di SMA Negeri 8 Surakarta mempunyai tingkat kenakalan remaja yang termasuk kategori rendah (45,1%); dan 3) Terdapat hubungan antara pola asuh orang tua dengan kenakalan remaja di SMA Negeri 8 Surakarta (t = -0,520; Zhitung = -7,300 < -2,58; p= 0,000 < 0,05). Pola asuh orang tua mempunyai hubungan dengan kenakalan remaja di SMA Negeri 8 Surakarta. Kata kunci: pola asuh orang tua, kenakalan remaja.